Dyrk1a regulates the cardiomyocyte cell cycle via D-cyclin-dependent Rb/E2f-signalling. Issue 3 (7th April 2016) - Hille, Susanne; Dierck, Franziska; Kühl, Constantin; Sosna, Justyna; Adam-Klages, Sabine; Adam, Dieter; Lüllmann-Rauch, Renate; Frey, Norbert; Kuhn, Christian
Abstract: Aims: Down syndrome-associated dual-specificity tyrosine-(Y)-phosphorylation-regulated kinase 1A (DYRK1A) is a ubiquitously expressed protein kinase. Up to date a variety of targets have been identified, establishing a key role for Dyrk1a in selected signalling pathways. In cardiomyocytes, Dyrk1a acts as a negative regulator of hypertrophy by phosphorylating transcription factors of the NFAT family, but its mechanistic function in the heart remains poorly understood. This study was designed to investigate a potential protective role of Dyrk1a in cardiac hypertrophy in vivo . Methods and results: We generated transgenic mice with cardiac-specific overexpression of Dyrk1a. Counterintuitively, these mice developed severe dilated cardiomyopathy associated with congestive heart failure and premature death. In search for the cause of this unexpected phenotype, we found that Dyrk1a interacts with all members of the D-cyclin family and represses their protein levels in vitro and in vivo . Particularly, forced expression of Dyrk1a leads to increased phosphorylation of Ccnd2 on Thr280 and promotes its subsequent proteasomal degradation. Accordingly, cardiomyocytes overexpressing Dyrk1a display hypo-phosphorylated Rb1, suppression of Rb/E2f-signalling, and reduced expression of E2f-target genes, which ultimately results in impaired cell cycle progression. Conclusions: We identified Dyrk1a as a novel negative regulator of D-cyclin-mediated Rb/E2f-signalling. As dysregulation of this pathway with impaired cardiomyocyte proliferation leads to cardiomyopathy, dose-specific Dyrk1a expression and activity appears to be critical for the hyperplastic and hypertrophic growth of the developing heart.